2019
DOI: 10.1097/bpo.0000000000000964
|View full text |Cite
|
Sign up to set email alerts
|

Gross Motor Skills in Children With Idiopathic Clubfoot and the Association Between Gross Motor Skills, Foot Involvement, Gait, and Foot Motion

Abstract: Level II-prognostic studies.This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-NC-ND), where it is permissible to download and share the work provided it is properly cited. The work cannot be changed in any way or used commercially without permission from the journal. http://creativecommons.org/licenses/by-nc-nd/4.0/.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 19 publications
3
33
0
2
Order By: Relevance
“…Based on preliminary evidence from previous smaller-scale studies and clinical experience, we expected a moderately increased frequency of neurodevelopmental challenges in children with idiopathic clubfoot versus general population controls. [11][12][13] Findings largely confirm our predictions and indicate a subtle-to-strong elevation of difficulties in children with idiopathic clubfoot for several neurodevelopmental domains, predominantly regarding motor skills, perception, and language, as well as the subdomains of gross and fine motor skills, relation in space, and comprehensive and expressive language skills. About one-third of the children with idiopathic clubfoot scored in the possibly clinically significant range in two or more neurodevelopmental domains.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Based on preliminary evidence from previous smaller-scale studies and clinical experience, we expected a moderately increased frequency of neurodevelopmental challenges in children with idiopathic clubfoot versus general population controls. [11][12][13] Findings largely confirm our predictions and indicate a subtle-to-strong elevation of difficulties in children with idiopathic clubfoot for several neurodevelopmental domains, predominantly regarding motor skills, perception, and language, as well as the subdomains of gross and fine motor skills, relation in space, and comprehensive and expressive language skills. About one-third of the children with idiopathic clubfoot scored in the possibly clinically significant range in two or more neurodevelopmental domains.…”
Section: Discussionsupporting
confidence: 80%
“…To the best of our knowledge, this is the first study to target neurodevelopmental difficulties in children with idiopathic clubfoot. Based on preliminary evidence from previous smaller‐scale studies and clinical experience, we expected a moderately increased frequency of neurodevelopmental challenges in children with idiopathic clubfoot versus general population controls . Findings largely confirm our predictions and indicate a subtle‐to‐strong elevation of difficulties in children with idiopathic clubfoot for several neurodevelopmental domains, predominantly regarding motor skills, perception, and language, as well as the subdomains of gross and fine motor skills, relation in space, and comprehensive and expressive language skills.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…These findings agree with previous studies. 10 11 Lööf et al 14 also found no difference between clubfoot laterality when analyzing motor development until the age of 5 years old.…”
Section: Discussionmentioning
confidence: 96%